Institutionalization of the Approval Principle of Majority Creditors for Bankruptcy Decisions in Bankruptcy Act Reform Efforts - Rian Saputra; Resti Dian Luthviati (Journal of Morality and Legal Culture, 2020)
This study aims to determine the urgency of institutionalizing the principle of bankruptcy decisions that must be approved by the majority creditors with a test stone in the form of a bankruptcy decision Number: 04/Pdt.Sus-PKPU/2018/PN.Niaga.Jkt.Pst then also to analyze the opportunities for institutionalizing the principle. mentioned in Indonesian law. This research is a normative legal research with an approach in the form of a conceptual approach, and a statute approach and a case approach. The results show that the urgency of applying the principle of "Approval of Bankruptcy Decisions Must be approved by Majority Creditors" in Indonesia is based on the Bankruptcy Decision Number: 04/Pdt.Sus-PKPU/2018/PN.Niaga.Jkt.Pst, in addition to following the development of global bankruptcy law. , also in order to provide justice to fellow creditors so that no creditor feels aggrieved in any future bankruptcy decisions. The principle itself requires that each bankruptcy decision be approved by at least 50% of the majority of creditors according to the number of claims (receivables), not the majority according to the number of people. Even though, the application for a bankruptcy statement was made by the Debtor himself, the bankruptcy decision should not have been taken by the court without the approval of the creditors or the majority of creditors. Also, the opportunity to apply this principle in Indonesia is very possible considering that the principle is in accordance with the character of the nation which clearly makes consensus & deliberation as an alternative in every problem that exists within the Indonesian nation, it is not wrong if this is also applied in the concept of the Bankruptcy Law in the future (das sein).